Assessment of Hexavalent Chromium Pollution in Buriganga and Dhaleshwari River Waterbodies Adjacent to Tannery Estates in Bangladesh - Rahman, Hafizur; Hoque, Nabila; Sarker, Palash K; Safa, Ashrafus (MIST International Journal of Science and Technology, 2020)
Recently, in Bangladesh, all tannery industries have been relocated to a new location exclusively established for leather processing industries with modern manufacturing facilities and effluent treatment plants with standard probations. Effluents generated from the tannery industries are now being disposed of into the surrounding river water bodies. In this study, our goal was to investigate the presence of chemical contaminants like hexavalent chromium (Cr6+) in the water bodies surrounding tannery industries and to understand the possible role played by the tannery effluents in contaminating the river water bodies with Cr6+. Result analysis revealed the presence of an amount of Cr6+ (ranging from 0.01 mg/L to 3.54 mg/L) in the surrounding water bodes, which was far above the maximum permissible limit of Cr6+ (0.05 mg/L for surface water), set by the Environmental Protection Agency. It is therefore, plausible to assume that effluents from the tanneries play an important role in hexavalent chromium contamination of water bodies surrounding tannery industries.